Analisis Yuridis Balik Nama Sertifikat Tanah Ketika Pemegang Hak Meninggal Dunia dan Ahli Waris tidak Diketahui: Studi Putusan Pengadilan Negeri Bekasi Nomor: 67/Pdt.G/2025/PN.Bks - Azhar, Maritza; Lestari, Andini Tri; Ndarung, Marianus; Pratasik, Angely Patricia Putri; Putro, Muhammad Djomy Dwi; Sadili, Akhmad; Yustika, Luthy (Media Hukum Indonesia (MHI), 2026)
Bekasi District Court Decision Number 67/Pdt.G/2025/PN Bks revealed administrative obstacles in the process of transferring the name on the land certificate, even though the sale and purchase transaction was legally valid. The plaintiff had obtained a Deed of Sale and Purchase (AJB), completed credit payments, and controlled the land since 2011, but the process was stalled because the previous owner had died and his heirs could not be identified. The judge accepted the lawsuit and ordered the National Land Agency (BPN) to carry out the transfer of name as a form of protection for buyers who acted in good faith, and emphasized the role of the courts as a solution when administrative procedures are unable to provide legal certainty.